Synergistic effect of antitumor activity of doxorubicin and bicomponent nanostructures based on aluminum oxide - O. V. Bakina; N. V. Svarovskaya; A. A. Miller; A. S. Lozhkomoev; A. V. Avgustinovich; А. Yu. Dobrodeev; L. V. Spirina; S. G. Afanasyev (Сибирский онкологический журнал, 2020)
Introduction. There are high-thech methods of nanoparticle production with controlled morphology and physical and chemical properties. Alumina-based mesoporous nanostructures have low toxicity and biocompatibility. FDI recommends alumina for biomedical application. Alumina inhibits the grow of cancer due to positive zeta-potential and low solubility in water. We observed the synergistic effect of joint application of doxorubicin and nanostructures. This approach reduces drug concentration and its toxicity.Purpose: to synthesize nanostructures with different surface potentials and to study toxicity of these nanostructures alone and in combination with doxorubicin.Material and Methods. The alumina-based nanostructures were obtained by the hydrolysis of nanopowder. The morphology of nanostructures was investigated by transmission electron microscopy with an integrated system of energy dispersive analysis. The phase composition of the particles was determined by x-ray diffraction. The effect of the synthesized nanostructures on the viability of cell lines was determined using the MTT test.Results. The synthesized nanostructures have a low toxicity and can be used as an adjuvant for doxorubicin.Conclusion. The combined use of doxorubicin and bicomponent nanostructures leads to an increase in the damaging effect of doxorubicin on Neuro-2a cells.